2016
DOI: 10.7554/elife.15258
|View full text |Cite
|
Sign up to set email alerts
|

The E3 ligase Ubr3 regulates Usher syndrome and MYH9 disorder proteins in the auditory organs of Drosophila and mammals

Abstract: Myosins play essential roles in the development and function of auditory organs and multiple myosin genes are associated with hereditary forms of deafness. Using a forward genetic screen in Drosophila, we identified an E3 ligase, Ubr3, as an essential gene for auditory organ development. Ubr3 negatively regulates the mono-ubiquitination of non-muscle Myosin II, a protein associated with hearing loss in humans. The mono-ubiquitination of Myosin II promotes its physical interaction with Myosin VIIa, a protein re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 78 publications
(114 reference statements)
1
43
0
Order By: Relevance
“…The SH2 domains directly recognize phosphotyrosine-containing sites on activated receptor protein kinases (RTKs) and cytoplasmic proteins. It has been suggested that the adaptor proteins Grb2/ Sem-5/drk provide a functional link between RTKs and activation of Ras signaling (10,17,18). The SH3 domains, particularly those located on the amino-terminal side of Grb2/Sem-5/drk, bind the C-terminal tail of the Sos protein (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SH2 domains directly recognize phosphotyrosine-containing sites on activated receptor protein kinases (RTKs) and cytoplasmic proteins. It has been suggested that the adaptor proteins Grb2/ Sem-5/drk provide a functional link between RTKs and activation of Ras signaling (10,17,18). The SH3 domains, particularly those located on the amino-terminal side of Grb2/Sem-5/drk, bind the C-terminal tail of the Sos protein (8).…”
Section: Discussionmentioning
confidence: 99%
“…5B). To overcome the lethality of homozygous flies and to determine the function of drk in the JO, we generated mosaic animals (eyFLP; drk Δ ) with a homozygous deletion of drk in the antenna and the eye but heterozygous in the rest of the body through flippase/flippase recognition target (Flp/FRT)-mediated mitotic recombination using the eyFLP system (18). We observed severe locomotor deficits in mosaic flies suggesting strong defects in gravity sensing as the main reason for the climbing defects because the JO is homozygous for drk Δ whereas the body (neuromuscular tissue) is heterozygous (Fig.…”
Section: The Pgln104leu Variant Most Likely Alters Interactions Of Gmentioning
confidence: 99%
“…The Drosophila genome harbors homologs of several Usher genes and some of these have been characterized in Johnston's organ ( Table 2 ). The Drosophila homolog of myosin VIIA [ myosin VIIA ; also known as crinkled ( ck )] is required for hearing: loss of ck abolishes a fly's auditory responses and causes the scolopidia to detach from the cuticle of the a2/a3 antennal joint in Johnston's organ ( Li et al, 2016 ; Todi et al, 2005 , 2008 ) ( Fig. 4 ).…”
Section: Conservation Of Usher Syndrome Proteins and Their Interactiomentioning
confidence: 99%
“…With regard to renal manifestations, it has been shown that MYH9 mutations affect podocytes attaching to the basement membrane through focal adhesion formation and result in their detachment, which is the main cause of proteinuria . Finally, functional myosin IIA is required to ensure that sensory cells in the inner ear respond correctly to sound by detecting air vibrations and converting them into electrical impulses .…”
Section: Essential Features Of Inherited Thrombocytopaenias Predisposmentioning
confidence: 99%